Nihilism and Violence in the Age of Technology: A Historical Diagnosis from Heidegger’s Critique of Metaphysics - Pérez Espigares, Pablo (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
This article tries to throw light on the ultimate roots of violence currently hitting our technological civilization. For this purpose we will analyze to what extent western philosophical tradition, beginning from its metaphysical core, has restricted the power of nothingness and how, as a consequence, it has favoured a biased view of nihilism that generates the perfect framework for the development of its destructive consequences. Following Heidegger's reflection, we will examine his «essential thinking» proposal as a way to overcome nihilism. We will then be able to arrive at its originary meaning and  penetrate into the essential origin of present-day violence.
Keywords: nihilism; metaphysics; violence; technology